The effect of vinasse on the growth performance and feed digestibility of Holstein male calves (Acta Scientiarum. Animal Sciences, 2019)
Industrial effluents of alcohol production are problematic for the environment. One of the proposed solutions to the reduction of harmful effects of the wastewater is to convert it into vinasse. The purpose of the present study is to investigate effects of rations with different levels of vinasse as a source of protein in the diet of 28 male Holstein calves, previously health checked, with an average initial weight of 300 ± 22.56 kg and the maximum similarity of weight and age. The calves were divided randomly into four treatments varied in vinasse (substituted for cottonseed meal): 0 (control), 5, 10 and 15 % with seven replications and each group was given its own specific diet for 110 days. Growth performance, nutrient digestibility and feed intake were examined. Final body weight, average daily weight gain and dry matter intake were significantly higher in calves fed diet with 10% vinasse compared to other treatments (p < 0.05). Rumen pH significantly increased in treatment four (15% vinasse) (p < 0.05). Crude fat, NDF, non-fiber carbohydrate (NFC) and dry matter digestibility didn’t show any significant difference between treatments (p > 0.05), but treatments with 10 and 15% vinasse significantly increased organic matter andcrude protein digestibility compared with control (p < 0.05). Totally substituting cottonseed meal with 10% vainasse in calves diet improved body weight gain and organic matter digestibility without any significant effects on rumen pH.